Structural motives controlling the binding affinity of 9, 10-bis(methylpyridinium)anthracenes towards DNA. Issue 8 (15th April 2020) - Fudickar, Werner; Linker, Torsten
Graphical abstract: Abstract: In the search of new DNA groove binding agents a series of substituted 9, 10-methylpyridiniumanthracenes have been synthesized and their interactions with DNA have been studied by UV/vis absorption, CD and fluorescence spectroscopy. A minor groove binding mode is confirmed by DNA melting studies, strong CD effects, the dependence of the binding affinity on ionic strength, and the differentiation between AT and GC base pairs. No binding occurs to GC sequences. Binding constants to calf thymus DNA (ct-DNA) and poly(dA:dT) in the range between 1 × 10 4 and 3 × 10 5 M −1 have been determined. The binding strength decreases with the size of substituents attached at the anthracene site. Variation of the substitution pattern of the charged groups shows that methyl groups in meta position cause slightly stronger binding than methyl groups in para position. In contrast, with these groups in ortho position, no binding interaction has been observed. The strongest binding is achieved with an expansion of the peripheral heterocycle from pyridine to quinoline. Molecular modeling reveals the pivotal role of the substitution pattern: Anthracenes with para and meta pyridines align along the minor grooves. On the other hand, the ortho derivative adopts no groove-alignment.